My heart fills with happiness ebook - Gray Smith, Monique (2016)
★ "A quiet loveliness, sense of gratitude, and—yes—happiness emanate from this tender celebration of simple pleasures."—Publishers Weekly, starred review "Will leave the youngest readers gladly imagining what fills their own hearts with joy."—The New York Times The sun on your face. The smell of warm bannock baking in the oven. Holding the hand of someone you love. What fills your heart with happiness? This beautiful board book, with illustrations from celebrated artist Julie Flett, serves as a reminder for little ones and adults alike to reflect on and cherish the moments in life that bring us joy. International speaker and award-winning author Monique Gray Smith wrote My Heart Fills with Happiness to support the wellness of Indigenous children and families, and to encourage young children to reflect on what makes them happy. Available in French as J'ai le cœur rempli de bonheur and in Spanish as Mi corazón se llena de alegría.